Single voxel proton MR spectroscopy findings of typical and atypical intracranial meningiomas - (:unkn) unknown (ELSEVIER IRELAND LTD, 2006)
Purpose: To prospectively define proton magnetic resonance spectroscopy (MRS) findings of meningiomas, and describe the ability or inability of short- and long-echo MRS to differentiate typical and atypical meningiomas in vivo. Material and methods: Seventeen patients with pathologically confirmed typical meningiomas and six with atypical meningiomas were evaluated with conventional MR imaging and MRS before resection. MRS studies using point-resolved spectroscopy (PRESS) localisation, at short- and long-echo time (TR 2000 ms, TE: 30 and 144 ms, 64-96 acquisition) were acquired on a 1.5 T scanner. MRS data obtained from these patients were compared with histopathological findings. Mean cellular proliferation (MIB-1) antibody staining against the Ki-67 antigen was also determined in all meningiomas. Results: Prominent choline (Cho) was present in all meningiomas. Alanine (Ala) was observed in 21 cases of the 23 meningiomas. Acetylaspartate (NAA) and creatine (Cr) were either not observed or detected in minimal amounts in at all both groups of meningiomas on long TE (144 ms) spectra. The mean Cho/Cr values in the four atypical meningiomas were 4.44 +/- 0.30 (mean standard deviation) and 3.39 +/- 0.52 in the 12 typical meningiomas on short TE spectra. Cho/Cr ratio could not be determined in the other seven cases because of a lack of creatine peak. Of the five meningiomas in which a lactate peak was detected, four were in typical cases and only one was in atypical meningioma. Mean MIB-1 proliferation index was 3.7% in typical meningiomas and 10% in atypical meningiomas. Conclusion: Prominent Cho, absence or low amount of NAA and Cr, and presence of Ala were common characteristics of spectral pattern of both atypical and typical meningiomas on MRS. MRS cannot reliably differentiate typical intracranial meningiomas from atypical meningiomas preoperatively. Mean MIB-1 proliferation index was well correlated with histopathology findings. (C) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: meningiomas; magnetic resonance imaging; magnetic resonance spectroscopy; brain; adults; MAGNETIC-RESONANCE SPECTROSCOPY; HUMAN BRAIN-TUMORS; MALIGNANT MENINGIOMAS; CONSISTENCY; DIAGNOSIS; PATTERNS